Equilibrium Non-Oil Current Account Assessments for Oil Producing Countries - Thomas, Alun (IMF Working Papers; Working Paper ;, 2008)
This paper introduces a methodology for assessing external balance in countries with large stocks of non-renewable resources based on oil stock data, and applies it to selected oil producing countries. The methodology uses a stock approach (instead of the more traditional flow approach) to estimate the equilibrium non-oil current account consistent with optimal consumption smoothing. One of the benefits of the stock approach is that geological data for oil reserves can be used to estimate oil wealth; however, the methodology makes the estimated non-oil current account norm very sensitive to oil price projections. Based on an oil price about USD 70 per barrel prevailing in the summer of 2007, the baseline estimates indicate that the non-oil current accounts for most of the countries in the sample are broadly in equilibrium. By the same token, using oil price projections as of the summer of 2008 implies large disparities between the equilibrium non-oil current account position and the medium term forecast for all countries in the sample except for Malaysia.